A systematic review and meta-analysis on the efficacy and safety of finerenone in the progression of heart failure - Peng, Shengtian; Li, Peipei; Yu, Zhixi; Du, Beibei; Yang, Ping (Frontiers in Pharmacology, 2025)
AimsFinerenone, a kind of mineralocorticoid receptor antagonist (MRA), may benefit heart failure (HF) patients as MRAs are established effective therapies for HF. Many studies have confirmed the drug’s effectiveness in treating kidney disease. However, the efficacy and safety of finerenone on HF remain unclear. Therefore, this systematic review and meta-analysis was conducted to assess the preliminary efficacy and safety of finerenone in HF treatment.MethodsThis systematic review and meta-analysis included randomized controlled trials (RCTs) involving adults with heart failure, diabetes, or chronic kidney disease (CKD) treated with finerenone. The major outcomes were the risk of HF occurrence or worsening and hospitalization due to HF, whereas the secondary outcomes included cardiovascular death and all-cause mortality. Data were extracted and analyzed following PRISMA guidelines, and risk of bias was evaluated using the Cochrane Handbook. This review was registered with the International Prospective Register of Systematic Reviews (PROSPERO; CRD42024612580).ResultsSix RCTs (n = 21, 295) were included. Finerenone was associated with a lower risk of HF occurrence or worsening and hospitalization due to HF than placebo [risk rate (RR): 0.81; 95% confidence interval (CI): 0.76–0.87; P < 0.00001]. However, no prominent differences were found in cardiovascular death (RR: 0.93; 95% CI: 0.83–1.03; P = 0.18) or all-cause mortality (RR: 0.94; 95% CI: 0.87–1.02; P = 0.11). Safety analysis indicated a reduced risk of serious adverse reactions (RR: 0.93; 95% CI: 0.90–0.98; P = 0.005) and discontinuation of the study medication due to adverse events (RR: 1.14; 95% CI: 1.01–1.30; P = 0.04).ConclusionFinerenone appears to decrease the risk related to HF occurrence and progression, particularly in patients with CKD and diabetes, but its impact on overall mortality remains uncertain. The potential benefits need to be balanced against the risk of adverse effects. Further research is essential to explore optimal dosing and treatment duration.